The effects of brick walls strengthened with perforated steel plates on frame behavior. (15th June 2019) - Özbek, Eray; Aykaç, Bengi; Aykaç, Sabahattin
Highlights: Strengthened specimens reached drift ratios 7.5% without significant strength loss. Increase of strength up to twice the reference was obtained. Increase of energy dissipation up to five times the reference was observed. Strengthening method can be applied without too much disturbance to the residents. Abstract: Some bays of reinforced concrete (RC) buildings are mostly infilled with brick walls according to architectural demands. The brick infill walls are generally not considered load-bearing members, but they are known to increase the strength and stiffness of the structure under seismic loads. However, this contribution can be provided at rather low story drifts, since brick is a quite brittle construction material. The present study aimed at improving the seismic performance of structure by strengthening the infill walls of the RC frame with perforated steel plates which is quite ductile. A total of 14 half-scale test specimens, including two references (an RC frame and an RC frame with infill wall) and 12 strengthened specimens, were tested under reversed cyclic lateral loading. Strengthened specimens exhibited ductile behavior and no significant loss in strength observed up to 7.5% drift ratio. In addition to the attained ductile behavior, increases in the strength reaching two times the reference value were obtained. Hence, this easily-applicable method, which can be applied without too much disturbance to the residents, is claimed to have the potential to be used for strengthening numerous RC structures in the future.